(untitled) (Interdisciplinary Studies Journal, 2023)
The present study performed photogrammetry of mandibles belonging to the osteological collection of the Center for Studies in Forensic Anthropology of the Faculty of Dentistry of the University of Pernambuco (CEAF/FOP/UPE) to verify its applicability for sexual diagnosis. A total of 100 mandibles from skeletons aged over 20 years, of both sexes, with intact mandibular ramus and condyle regions, were examined. Photographic images were obtained, followed by 3D mesh generation processing, through software and virtual measurement of each piece, as well as measures of the ramus and condyle of the mandibles in a physical way, for comparison with the digital method. The data were analyzed using descriptive and exploratory statistics and compared with the manual measurements of the bone pieces, obtaining a significant similarity between the variables: MnRB-D, MnRB-E, MxRB-D, MxRB-E, CC-D, CC-E, LC-D, LC-E, with a standard deviation between 1.2 and 4.0 mm and a general mean with a variance between 0.1 and 0.9 mm. The jaw photogrammetry technique, and its consequent measurement, can complement the human identification expertise in the investigation of sexual diagnosis, obtaining an accuracy of 68.9% for the manual model and 72.4% for the virtual one through logistic regression script.